Structural and Optical Properties of Co-Doped ZnO Nanoparticles Synthesized by the Sol-Gel Method - Nguyen Thi Phuong Loan; Lee Hsiao-Yi; Phan Thi Minh Man (Indonesian Journal of Material Research, 2026)
ZnO is recognized as a wide-bandgap semiconductor (3.37 eV) possessing a relatively huge exciton binding power (~60 meV), which makes it highly attractive for optoelectronic technologies. According to the current study, Co-incorporated ZnO nanoparticles were fabricated through an economical sol-gel synthesis route. The structural and optic characteristics were comprehensively underwent examination using XRD, SEM, and UV-Vis methods. Diffraction results reveal that all synthesized samples retain a pure hexagonal wurtzite phase, with no evidence of secondary phases, confirming effective Co incorporation into the ZnO lattice. As the Co concentration increases, a slight reduction in crystallite size is observed, indicating lattice distortion induced by dopant atoms. SEM analysis shows that the particles are predominantly quasi-spherical with minor agglomeration, and doping does not significantly alter their morphology. From an optical perspective, increasing Co content causes the absorption edge to shift toward longer wavelengths, accompanied by stronger absorption in the visible region. Bandgap values, extracted using Tauc analysis, reduce from 3.18 eV (undoped ZnO) to 2.94 eV at 3 mol% Co, followed by a marginal increase at higher concentrations. This trend is associated with the introduction of impurity-related electronic states within the bandgap. Overall, Co incorporation provides an effective means to modulate the optical response of ZnO nanostructures, thereby enhancing their suitability for advanced optoelectronic applications.